Arranjos institucionais e a burocracia de infraestrutura: Notas para uma história sobre a construç\~ao das capacidades estatais no Brasil - Ciro Campos Christo Fernandes; Mauro Santos Silva; Bruno Queiroz Cunha; Pedro Assumpç\~ao Alves (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– The paper is an exploratory historical analysis, based on documentary research and literature review, which focuses on the formation of the bureaucratic apparatus in the area of economic infrastructure, analyzed from the perspective of the construction of the Brazilian State and its technical, administrative and political capacities. The work explores the links between successive institutional arrangements and the construction of state capabilities of a technical and political nature. The trajectory of the institutional arrangements is analyzed based on a periodization that considers the inflections in the recent trajectory of the structuring of State functions, correspondingly, the organization of the public administration, its legal frameworks and institutional arrangements in each period. The periodization distinguishes the following moments: the beginnings of developmentalism (1930-1945); the parallel administration and developmental initiatives (1946-1963); state enterprises and the developmental State (1964-1988); and the emergence of the regulatory State and the resurgence of state activism (1988-2016). In the end, the conclusion is that it is dominant during most of the period analyzed the persistence of a vector of construction of the State apparatus that dislocates the formation of the bureaucracy away from the central administration.
Keywords: H83; N46; O21; P11; D73; H54; 330; bureaucracy; infrastructure; institutional arrangements; state capacities; economic development